Next generation sequencing yields the complete mitochondrial genome of the Zebra moray, Gymnomuraena zebra (Anguilliformes: Muraenidae). (1st November 2016) - Loh, Kar-Hoe; Shao, Kwang-Tsao; Chen, Hong-Ming; Chen, Ching-Hung; Chong, Ving-Ching; Loo, Poh-Leong; Shen, Kang-Ning; Hsiao, Chung-Der
Abstract: In this study, the complete mitogenome sequence of the Zebra moray, Gymnomuraena zebra (Anguilliformes: Muraenidae) has been sequenced by the next-generation sequencing method. The assembled mitogenome consisting of 16, 576 bp includes 13 protein coding genes, 22 transfer RNAs, and two ribosomal RNAs genes. The overall base composition of Zebra moray is 30.2% for A, 26.8% for C, 17.2% for G, and 25.8% for T and show 80% identities to Kidako moray, Gymnothorax kidako. The complete mitogenome of the Zebra moray provides an essential and important DNA molecular data for further phylogeography and evolutionary analysis for moray eel phylogeny.